2011
DOI: 10.1088/1674-0068/24/02/211-217
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Low-temperature Steam Reforming of Bio-oil over Ni/HZSM-5 Catalyst

Abstract: We investigated high catalytic activity of Ni/HZSM-5 catalysts synthesized by the impregnation method, which was successfully applied for low-temperature steam reforming of bio-oil. The influences of the catalyst composition, reforming temperature and the molar ratio of steam to carbon fed on the stream reforming process of bio-oil over the Ni/HZSM-5 catalysts were investigated in the reforming reactor. The promoting effects of current passing through the catalyst on the bio-oil reforming were also studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is generally accepted that the HZSM-5 zeolite is very active for deoxygenation and C−C cracking. Using 20 wt % Ni/ HZSM-5, Qiu et al 44 achieved a H 2 yield of ∼90% with nearly complete conversion of crude bio-oil (CH 2.03 O 0.67 •0.89H 2 O) at 450 °C and a S/C ratio of 17, which was much higher than that of the Ni/Al 2 O 3 catalyst at ∼60% conversion. The H 2 yield for the catalyst, however, reached a value of ∼99.8% at 600 °C.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…It is generally accepted that the HZSM-5 zeolite is very active for deoxygenation and C−C cracking. Using 20 wt % Ni/ HZSM-5, Qiu et al 44 achieved a H 2 yield of ∼90% with nearly complete conversion of crude bio-oil (CH 2.03 O 0.67 •0.89H 2 O) at 450 °C and a S/C ratio of 17, which was much higher than that of the Ni/Al 2 O 3 catalyst at ∼60% conversion. The H 2 yield for the catalyst, however, reached a value of ∼99.8% at 600 °C.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…For biomass gasification, nickel supported on Al2O3 catalysts have been reported to have higher activity compared with nickel supported on MgO, TiO2, CeO2 and ZrO2 [33], ZrO2, MgO, TiO2, SiO2 [54]. In addition, nickel has also been supported on other materials, for example, dolomite [55,56], char [37,57,58], olivine [59], ceramic foam [60], mayenite [61], HZSM-5 [62] and MCM-41 [63].…”
Section: Deactivation Of Nickel-based Catalystsmentioning
confidence: 99%
“…Therefore, hydrogen production using bio-oil is more economically feasible. So far, much research into the steam reforming of bio-oil for producing hydrogen has been reported (Aktas et al, 2010;Qiu et al, 2011;Rioche et al, 2005;Takanabe et al, 2004;Wang et al, 1997;Wu and Liu, 2011).…”
Section: Introductionmentioning
confidence: 99%